2016
DOI: 10.3389/fpsyg.2015.02059
|View full text |Cite
|
Sign up to set email alerts
|

How Victim Sensitivity leads to Uncooperative Behavior via Expectancies of Injustice

Abstract: According to the Sensitivity-to-mean-intentions model, dispositional victim sensitivity involves a suspicious mindset that is activated by situational cues and guides subsequent information processing and behavior like a schema. Study 1 tested whether victim-sensitive persons are more prone to form expectancies of injustice in ambiguous situations and whether these expectancies mediate the relationship between victim sensitivity and cooperation behavior in a trust game. Results show an indirect effect of victi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 24 publications
3
17
0
Order By: Relevance
“…Prior studies have shown that victim sensitivity can be an antecedent variable that affects altruistic behavior, and similar results have been observed in social decision-making settings (Maltese et al., 2016). The present study extended such findings to the Chinese educational context.…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…Prior studies have shown that victim sensitivity can be an antecedent variable that affects altruistic behavior, and similar results have been observed in social decision-making settings (Maltese et al., 2016). The present study extended such findings to the Chinese educational context.…”
Section: Introductionsupporting
confidence: 73%
“…Such individuals are motivated to avoid being exploited and thus perform fewer altruistic, collaborative, and cooperative behaviors (Gollwitzer and Rothmund, 2009; Gollwitzer et al., 2013). This theoretical model has been demonstrated in several studies (Traut-Mattausch et al., 2011; Baumert et al., 2012; Maltese et al., 2016). For example, in a workplace environment, researchers found that victim-sensitive individuals tended to perceive more unfair treatment by their employers (Schmitt and Dörfel, 1999).…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…Regarding victim sensitivity, it is reasonable to assume that, when confronted with untrustworthiness cues, victim-sensitive individuals initially show avoidance-oriented reactions such as an increased attentional vigilance toward untrustworthiness. Prior research has shown that, even in the absence of an untrustworthiness prime, victim-sensitive persons show a greater attentional vigilance toward justice- and injustice-related semantic concepts ( Baumert et al, 2012 ), and more recent research shows that, in the presence of an untrustworthiness prime (i.e., a victimization experience), victim-sensitive individuals are more likely to associate ambiguous social situations with injustice ( Maltese et al, 2014 ). Especially the latter finding is in line with the notion that victim-sensitive individuals show avoidance-oriented reactions after being confronted with untrustworthiness cues.…”
Section: How Does Victim Sensitivity Perpetuate Itself Across Social mentioning
confidence: 99%
“…On the one hand, the player’s emotional state may be the reason for the rejection of unfair offers in the UG. For example, using clips (Harle and Sanfey, 2007; Andrade and Ariely, 2009), emotional pictures (Moretti and Di Pellegrino, 2010), imaging (van den Bos, 2003), trait-valenced words (Maltese et al, 2016), and unpleasant smells (Bonini et al, 2011) to arouse emotion, previous studies have shown that inducing positive emotion increases the acceptance rates of unfair offers, whereas inducing negative emotion decreases the acceptance rates of unfair offers. Furthermore, correlation analysis has found that negative emotion is significantly correlated with unfairness ratings (Pillutla and Murnighan, 1996).…”
Section: Introductionmentioning
confidence: 99%